A Strategy for Character Building Among Rahmatan Lil'alamin Students in Madrasah Ibtidaiyah, Utilising the Ut-10 Approach - Hasanah, Mila; Shalihah, Siti; Assyauqi, Moh Iqbal; Tamimah, Hafizah (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2025)
The study aimed to develop the UT-10 Learning Model to enrich the character profiles of Rahmatan lil'Alamin students within South Kalimantan's Madrasah Ibtidaiyah institutions. The research followed a structured methodology involving defining, designing, developing, and disseminating stages (4D). The defining phase encompassed thorough analysis and needs assessment across multiple Madrasah Ibtidaiyah, establishing a nuanced understanding of their specific requisites. Moving into the design phase, meticulous planning crafted a model centered on enhancing student character profiles, integrating values like Ta'addub and Qudwah while incorporating local knowledge. Validation by experts affirmed the model's feasibility, prompting minor adjustments that were duly integrated. Through trials and large-scale tests across diverse locations, the UT-10 model consistently proved effective, scoring an average of 89.09% in fortifying students' character profiles. Notably, pivotal stages within the model, particularly the Uswah and Ta'lim phases, demonstrated potential in nurturing essential character traits among students. In conclusion, this research showcased the adaptability and efficacy of the UT-10 Learning Model in fostering holistic student development within Madrasah Ibtidaiyah, paving the way for a comprehensive educational approach focused on enhancing character profiles.